2017
DOI: 10.1111/mcn.12516
|View full text |Cite
|
Sign up to set email alerts
|

Children concurrently wasted and stunted: A meta‐analysis of prevalence data of children 6–59 months from 84 countries

Abstract: Children can be stunted and wasted at the same time. Having both deficits greatly elevates risk of mortality. The analysis aimed to estimate the prevalence and burden of children aged 6–59 months concurrently wasted and stunted. Data from demographic and health survey and Multi‐indicator Cluster Surveys datasets from 84 countries were analysed. Overall prevalence for being wasted, stunted, and concurrently wasted and stunted among children 6 to 59 months was calculated. A pooled prevalence of concurrence was e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
142
3
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(175 citation statements)
references
References 20 publications
(25 reference statements)
18
142
3
2
Order By: Relevance
“…This analysis demonstrates that key determinants of child stunting are also significant determinants of child wasting in South Asia. This supports the view that these two manifestations of undernutrition should not be separated conceptually or programmatically (Bergeron & Castleman, ; Khara et al, ). Both forms of undernutrition are the result of multifaceted and overlapping processes by which children face physiological and developmental insults at individual, maternal, family, and societal levels.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…This analysis demonstrates that key determinants of child stunting are also significant determinants of child wasting in South Asia. This supports the view that these two manifestations of undernutrition should not be separated conceptually or programmatically (Bergeron & Castleman, ; Khara et al, ). Both forms of undernutrition are the result of multifaceted and overlapping processes by which children face physiological and developmental insults at individual, maternal, family, and societal levels.…”
Section: Discussionsupporting
confidence: 80%
“…Thus, there is an urgent call to not only capture the prevalence and programme coverage of this co‐occurrence but also understand the joint aetiology. There are important gaps in our understanding of the direction and nature of the relationship between wasting and stunting, and it is possible that interventions for either form of malnutrition may affect the other (Angood, Khara, Dolan, Berkley, & WaSt Technical Interest, ; Khara, Mwangome, Ngari, & Dolan, ). Although there is evidence that maternal nutritional status during pregnancy and stature both play critical roles in determining the baby's length and weight at birth (Black et al, ), the research prioritization exercise conducted by Angood et al () highlighted a need for studies designed to understand the origins of wasting and stunting and the programmatic opportunities and implications of breaking the intergenerational cycle of undernutrition.…”
Section: Introductionmentioning
confidence: 99%
“…The burden of stunting and the concurrence of stunting and severe wasting, observed in this population, have not been well described but were particularly high: Among severely wasted children, 79% were stunted, and 49% were severely stunted. In an analysis of nationally representative data from 84 countries, Niger was found to have the highest rate of concurrence of wasting and stunting globally (8%, 95% CI: [7.2, 8.9]) (Khara et al, ). The high rate of concurrence observed in our analysis underscores how concurrent severe wasting and stunting can be concentrated in the most vulnerable populations of severely malnourished children.…”
Section: Discussionmentioning
confidence: 99%
“…Wasting is predominantly caused by acute nutrient deficiency and infection but shares many causal pathways with stunting (Briend, Khara, & Dolan, 2015;Martorell & Young, 2012). Wasting and stunting can often coexist in the same child (Khara, Mwangome, Ngari, & Dolan, 2017). Although each condition is associated with an increased risk of death, it has been shown that the risk is multiplicative when such anthropometric deficits are concurrent (McDonald et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Providing an in-depth analysis of the latter proves problematic, particularly in sub-Saharan Africa where the low prevalence of triple failure (mostly between 2% and 4%), combined with the small sample size lead to large margins of error, even at the national level. (Khara et al, 2017) underestimates the extent of multiple malnutrition by omitting children who experience Underweight and Stunting (but not Wasting), who account for 14% of all children in the region. Similarly, another 4% of children are wasted and underweight (but not stunted).…”
Section: Multiple Malnutritionmentioning
confidence: 99%